Dialectics of Religion and Tradition in Determining the Marriage Day of Javanese Muslims in Papua Province - Isrowiyah, Isrowiyah; Fauziah, Silvi Laila Rista; Yusuf, Muhamad; Zulihi, Zulihi; Taslim, Muhammad; Watora, Ibrahim; Hermansyah, Hermansyah (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This research aims to explore the weton tradition in determining the auspicious day for marriage in Javanese Muslims society, particularly in Arso IX, Papua Province, and its impact on the social and spiritual life of the community. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. The results show that the weton tradition has a deep philosophical value, serves as a guide in determining auspicious days, and strengthens cultural identity and social ties among the community. From a social perspective, the use of weton calculation in marriage can be understood as the parents' desire to choose the best partner for their children. The wedding day carried out based on weton calculations is still considered valid as long as it fulfils the pillars and conditions stipulated in Islamic law, without violating the principles of the Islamic religion. This research confirms the importance of dialog between religious teachings and traditional practices in preserving the harmonious relationship between religious social practices and lokan cultural wisdom.